Development of polysaccharide bioplastic: Analysis of thermo-mechanical properties and different environmental implications - Abe, Mateus Manabu [UNESP]; Portinho, Jorge Laço [UNESP]; Gonçalves, Matheus de Moraes Cunha [UNESP]; Sanvezzo, Paula Bertolino; Freitas, Caroline de [UNESP]; de Souza, Joyce Faria [UNESP]; Carneiro, Ruan; Ferragut, Carla; Costa, Michelle Leali [UNESP]; Aouada, Marcia Regina de Moura [UNESP]; Branciforti, Marcia Cristina; Freire, Cintia Cristina da Costa [UNESP]; et al. (Elsevier, 2024)
Despite the distinct benefits of plastics, the environmental impacts stemming from their production and accumulation in the environment have become a global concern. Therefore, the development of new technologies that mitigate these impacts is of notable importance. The present study aimed to evaluate the physicochemical properties of starch-xylan-based bioplastic, and to discuss the viability of this material in terms of applications and ecological impacts. Holocellulose, xylan, and α-cellulose were extracted from waste biomass and combined with starch for bioplastic production. Solubility in food simulants (3% acetic acid, and 90% ethanol) was performed for xylan and starch-based bioplastics. Bioplastic was evaluated to grow Aspergillus versicollor for xylanase production. The bioplastic was evaluated as a photoprotector with yeast exposed to UVC light-covered by the bioplastic for 2 h. Bioplastic disintegration was evaluated in different soil moistures and the disintegration on the surface of the compost. Liquid washes from soils exposed to bioplastic biodegradation were tested for Lactuca sativa seed germination/inhibition. Water from a local lake was exposed to bioplastic and microbial cell density modification was verified. Images of the surface of the bioplastics were obtained by scanning electron microscopy, and characterized by thermogravimetric and dynamic-mechanical analysis. The xylan addition in bioplastic led to a material with a 40–50% decreased ultraviolet light transmittance. An increase in xylan concentration reduced solubility in lipid food simulant solutions, with no fatty solubilization with 25% of xylan. It suggests potential applications in photoprotective and packaging contexts. The thermal degradation temperature of the pure starch bioplastic was 324 °C, and the addition of 10% (287 °C), 15% (286 °C), and 25% (296 °C) xylan (w/w) indicated a reduction in thermal resistance, possibly due to suboptimal interaction between polymer chains. The decrease in crystallinity in the compositions 10/90% (Xc = 20%), 15/85% xylan/starch (Xc = 21%) compared to 25/75% xylan/starch (Xc = 11%) also underscored the complexity of polymer interactions within the bioplastic matrix. Tensile strength of pure starch was 1.21 MPa, while the composition of 15/85% xylan/starch exhibited improved strength 2.99 MPa. Further investigation into the interaction between starch and xylan is warranted. Concerning the disintegration of the 25/75% xylan/starch formulation in the soil, the humidity of the soil matrix played a significant role. The disintegration occurred over 5 days and 16 days in compost (55% humidity) and soil (32.6% humidity), respectively. The results of phytotoxicity (Lactuca sativa seeds) and changes in the physicochemical and biological profile of water (smell, turbidity, phosphorus and nitrogen levels, pH, and bacterial and phytoplankton density/richness), in response to exposure to bioplastics, highlight the necessity of developing this biologically-based and biodegradable technology in concerns about potential environmental impacts. Furthermore, the present study introduces the approach of bioplastic waste recycling using enzyme production biotechnology. In line with the legitimacy of bioplastics as important materials for addressing the challenges posed by their non-biodegradable synthetic counterparts, the presented results broaden the discourse on the feasibility of this biologically based material, contributing to the development of a sustainable society.